Clostridium septicum Aortitis and Cecal Adenocarcinoma - Brian Moseley; Nicola W. Mwirigi; Juan Bowen (Case Reports in Medicine)
Clostridium septicum aortitis is a rare infection that is highly associated with underlying malignancy. We present a case of an 82-year-old male diagnosed with both C. septicum aortitis and a high-grade cecal tubulovillous adenoma. The patient was offered aortic resection; however, he opted for only suppressive antibiotic therapy and a right hemicolectomy with ileocolonic anastomosis. He ultimately passed away 75 days following admission. The authors report on the connection between C. septicum aortitis and malignancy. The authors also discuss the need for prompt treatment with antibiotics once the infection is identified and the consideration of aortic resection given the risk of aneurysmal change with aortic dissection or rupture.